A = { x \(\in\)N } x = m\(^2\)( m + 5 ) ; m = 0;1;2;3}
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \({x^5}:{x^3} = {x^{5 - 3}} = {x^2}\);
b) \((4{x^3}):{x^2} = (4:1).({x^3}:{x^2}) = 4x\);
c) \((a{x^m}):(b{x^n}) = (a:b).({x^m}:{x^n}) = (a:b).{x^{m - n}}\)(a ≠ 0; b ≠ 0; m, n \(\in\) N, m ≥ n).
a) \(3{x^5}.5{x^8} = 3.5.{x^5}.{x^8} = 15.{x^{5 + 8}} = 15.{x^{13}}\).
b) \( - 2{x^{m + 2}}.4{x^{n - 2}} = - 2.4.{x^{m + 2}}.{x^{n - 2}} = - 8.{x^{m + 2 + n - 2}} = - 8.{x^{m + n}}\) (m, n \(\in\) N; n > 2).
N=\(\frac{2\sqrt{x}-9}{x-5\sqrt{x}+6}+\frac{2\sqrt{x}+1}{\sqrt{x}-3}+\frac{\sqrt{x}+3}{2-\sqrt{x}}\)
= \(\frac{2\sqrt{x}-9}{x-2\sqrt{x}-3\sqrt{x}+6}+\frac{2\sqrt{x}+1}{\sqrt{x}-3}-\frac{\sqrt{x}+3}{\sqrt{x}-2}\)
= \(\frac{2\sqrt{x}-9}{\sqrt{x}\left(\sqrt{x}-2\right)-3\left(\sqrt{x}-2\right)}+\frac{2\sqrt{x}+1}{\left(\sqrt{x}-3\right)}-\frac{\sqrt{x}+3}{\sqrt{x}-2}\)
= \(\frac{2\sqrt{x}-9}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}+\frac{\left(2\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}-\frac{\left(\sqrt{x}+3\right)\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)
ĐKXĐ : x ≠ 4 ; x ≠ 9
Rút gọn :
=\(\frac{2\sqrt{x}-9}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}+\frac{\left(2\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}-\frac{\left(\sqrt{x}+3\right)\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)
= \(\frac{2\sqrt{x}-9+\left(\sqrt{x}-2\right)\left(2\sqrt{x}+1-\sqrt{x}-3\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)
=\(\frac{2\sqrt{x}-9+\left(\sqrt{x}-2\right)\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)
= \(\frac{2\sqrt{x}-9+x-2\sqrt{x}+4}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)
= \(\frac{x-5}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)
Để N =5 thì :
<=> \(\frac{x-5}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\) =5
<=> x-5 = \(\left(5\sqrt{x}-10\right)\left(\sqrt{x}-3\right)\)
<=> x-5 = 5x - \(15\sqrt{x}\) - \(10\sqrt{x}\) +30
<=> x-5x-25\(\sqrt{x}\) =35
a) \(\sqrt{x}\ne3;\sqrt{x}\ne2\Rightarrow x\ne4;x\ne9\)
\(N=\frac{2\sqrt{x}-9}{x-5\sqrt{x}+6}+\frac{2\sqrt{x}+1}{\sqrt{x}-3}+\frac{\sqrt{x}+3}{2-\sqrt{x}}\)
\(\Leftrightarrow N=\frac{2\sqrt{x}-9}{\left(\sqrt{x}-3\right)\left(\sqrt{x}-2\right)}+\frac{2\sqrt{x}+1}{\sqrt{x}-3}-\frac{\sqrt{x}+3}{\sqrt{x}-2}\)
\(\Leftrightarrow N=\frac{2\sqrt{x}-9+2x-3\sqrt{x}-2-x+9}{\left(\sqrt{x}-3\right)\left(\sqrt{x}-2\right)}\)
\(\Rightarrow N=\frac{x-\sqrt{x}-2}{\left(\sqrt{x}-3\right)\left(\sqrt{x}-2\right)}=\frac{\left(\sqrt{x}-2\right)\left(\sqrt{x}+1\right)}{\left(\sqrt{x}-3\right)\left(\sqrt{x}-2\right)}=\frac{\sqrt{x}+1}{\sqrt{x}-3}\)
b) \(N=5\Leftrightarrow\frac{\sqrt{x}+1}{\sqrt{x}-3}=5\)
\(\Leftrightarrow\sqrt{x}+1=5\sqrt{x}-15\Leftrightarrow4\sqrt{x}=16\)
\(\Leftrightarrow\sqrt{x}=4\Rightarrow x=16\) (thỏa mãn)
c) \(N=\frac{\sqrt{x}+1}{\sqrt{x}-5}=\frac{\sqrt{x}-5+6}{\sqrt{x}-5}=1+\frac{6}{\sqrt{x}-5}\)
để N \(\in\) Z thì \(\left(\sqrt{x}-5\right)\inƯ\left(6\right)=\left\{\pm1;\pm2;\pm3;\pm6\right\}\)
\(\sqrt{x}-5\) | 1 | -1 | 2 | -2 | 3 | -3 | 6 | -6 |
x | 36 | 16 | 49 | 9 | 64 | 4 | 121 | loại |
[ ( 6 . x - 72 ) : 2 - 84 ] . 28 = 5628
( 6 . x - 72 ) : 2 - 84 = 5628 : 28
( 6 . x - 72 ) : 2 - 84 = 201
( 6 . x - 72 ) : 2 = 201 + 84
( 6 . x - 72 ) : 2 = 285
6 . x - 72 = 285 . 2
6 . x - 72 = 570
6 . x = 570 + 72
6 . x = 642
x = 642 : 6
x = 107
a) \({x^2}.{x^4} = {x^{2 + 4}} = {x^6}\).
b) \(3{x^2}.{x^3} = 3.1.{x^{2 + 3}} = 3{x^5}\).
c) \(a{x^m}.b{x^n} = a.b.{x^{m + n}}\) (a ≠ 0; b ≠ 0; m, n \(\in\) N).